Feed pellet production with locally availably products: IPSR Innovation Profile - Rudiger, Udo; Dhehibi, Boubaker; Frija, Aymen; Elayed, Monia (2023)
Feed pellet production for ruminants using a small-scale pelletizer and locally available agricultural products and agroindustrial by-products to replace expensive imported concentrates and reduce production costs, For agro-pastoralists (improved feed) and farmer organizations (income generation).